2016
DOI: 10.14311/app.2016.3.0075
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Change in the Mechanical Behavior of Synthetic Yarns Submitted to Consecutive Stiffness Tests

Abstract: Abstract. Anchoring systems of offshore platforms are designed to work uninterruptedly for 20 to 30 years, and despite the increasing number of studies concerning these systems' mechanical behavior in working conditions, most of them are conducted in speeding environments, due to the necessity of results in the short term. There are standardized stiffness tests, such as ISO 18692, based on quantities like Dynamic Stiffness and Quasi-static Stiffness, through which one can compare, quantitatively, two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Therefore, the aim of this paper is to provide an experimental-based prediction for the resistance of the main commercial synthetic fibres used for this application nowadays, by analyzing their endurance under certain cyclic loads. Seeking to predict the mechanical behaviour of the most commonly used synthetic fibres within this specific application, researches have been carried out to evaluate wear mechanisms such as creep at low temperatures [5] and stiffness [6] of these yarns. Thus, aiming to enhance the technical analysis on this paper, other tests besides fatigue were conducted, including creep, tensile and linear density (which allowed the determination of the linear tenacity).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of this paper is to provide an experimental-based prediction for the resistance of the main commercial synthetic fibres used for this application nowadays, by analyzing their endurance under certain cyclic loads. Seeking to predict the mechanical behaviour of the most commonly used synthetic fibres within this specific application, researches have been carried out to evaluate wear mechanisms such as creep at low temperatures [5] and stiffness [6] of these yarns. Thus, aiming to enhance the technical analysis on this paper, other tests besides fatigue were conducted, including creep, tensile and linear density (which allowed the determination of the linear tenacity).…”
Section: Introductionmentioning
confidence: 99%
“…Post-impact mechanical characterization of HMPE yarns Moreover, similar investigations have shown the mechanical behaviour of the most commonly used synthetic fibres (polyester, polyamide, aramid), assessing creep at low temperatures [10], stiffness [11], and fatigue [12][13][14] of yarns. Within this context, Louzada et al [15] showed that the fatigue life of polyester yarns decreases after dynamic loadings, depending on the magnitude of the impact.…”
Section: No /mentioning
confidence: 99%
“…Yarn-on-yarn abrasion is another (now a mechanical) degradation mechanism, even more relevant than the previous ones, that can affect the material's mechanical behaviour [7]. For characterisation purposes considering mooring ropes applications, static and dynamic stiffness of polymeric multifilaments are typically assessed according to ISO 18692 [8] and ISO 14909 [9,10].…”
Section: Introductionmentioning
confidence: 99%